Gastric Adenocarcinoma Presenting as a Rheumatoid Factor and Anti-cyclic Citrullinated Protein Antibody-Positive Polyarthritis: A Case Report and Review of Literature - Silvério-António, Manuel; Parlato, Federica; Martins, Patrícia; Khmelinskii, Nikita; Braz, Sandra; Fonseca, João Eurico; Polido-Pereira, Joaquim (Frontiers in Medicine, 2021)
A 64-year-old male presented with a six-month history of symmetric polyarthritis involving proximal interphalangeal joints and metacarpophalangeal joints of the hands, wrists and ankles. Associated symptoms included vomiting, progressive fatigue and weight loss. Laboratory results showed microcytic anaemia, leucocytosis, thrombocytosis, elevated C-reactive protein and erythrocyte sedimentation rate and rheumatoid factor (RF) and anti-cyclic citrullinated protein (ACPA) antibodies positivity. Joints radiographs were normal, without erosions. Upper endoscopy and gastric endoscopic ultrasonography showed a gastric adenocarcinoma with lymphatic involvement. Intraoperatively, peritoneal carcinomatosis was documented, and the patient started palliative chemotherapy. A paraneoplastic seropositive arthritis was assumed, and treatment with low-dose prednisolone and hydroxychloroquine was started. Arthritis remission was achieved and sustained up to 18 months of follow-up, although gastric cancer progression was documented. We describe a unique phenotype of paraneoplastic arthritis (PA) presenting as a seropositive (RF and ACPA positivity) rheumatoid arthritis (RA) with a good response to both low dose corticosteroids and hydroxychloroquine therapy. We also review the literature of PA, mostly the RA-like pattern, and the association between PA and ACPA positivity. This case highlights the importance of considering underlying cancer in elderly male patients, presenting with polyarthritis and systemic symptoms, even in those with ACPA positive RA-like arthritis.